Electrical Energy Saving and Management Initiatives: A Case Study of University Libraries in KPK, Pakistan - Hassan, A. Z.; Kamal, T.; Hassnain, S. R.; Ali, H.; Saleem, A. (The Nucleus, 2015)
Several recent studies show that a significant portion of the electrical energy consumption in educational institutes, residential and business buildings are due to the improper use of electrical appliances. The objective of this paper is to develop a cost effective automated power management system for the academic institutions to reduce the consumption of electrical energy. To this aim, a sensor-based intelligent system and decision making algorithm are proposed. As per algorithm, the system monitors the number of persons, intensity of light, temperature and accordingly controls the behavior of appliances. This paper includes a case study of two university libraries in KPK, Pakistan, namely, University of Engineering and Technology(UET), Peshawar, Abbottabad Campus and Hazara University Mansehra. The analysis of the experimental results concludes that the proposed energy saving system (PESS) is able to provide a significant energy savings.